2007
DOI: 10.1111/j.1461-0248.2007.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollination and other ecosystem services produced by mobile organisms: a conceptual framework for the effects of land‐use change

Abstract: Many ecosystem services are delivered by organisms that depend on habitats that are segregated spatially or temporally from the location where services are provided. Management of mobile organisms contributing to ecosystem services requires consideration not only of the local scale where services are delivered, but also the distribution of resources at the landscape scale, and the foraging ranges and dispersal movements of the mobile agents. We develop a conceptual model for exploring how one such mobile-agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
904
2
36

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 1,183 publications
(987 citation statements)
references
References 167 publications
5
904
2
36
Order By: Relevance
“…This heterogeneity can have important effects on agroecosystem processes by determining the persistence, distribution, dispersal, and interactions of farmland biodiversity [51,52]. These population-and community-level processes (determined by the response traits of species) can in turn affect ecosystem services through effect traits.…”
Section: Traits Across Spatial Scalesmentioning
confidence: 99%
“…This heterogeneity can have important effects on agroecosystem processes by determining the persistence, distribution, dispersal, and interactions of farmland biodiversity [51,52]. These population-and community-level processes (determined by the response traits of species) can in turn affect ecosystem services through effect traits.…”
Section: Traits Across Spatial Scalesmentioning
confidence: 99%
“…A number of studies have shown that pollinators use, and maybe even rely on, resources from crop fields and then return to natural habitats. Hence, agricultural habitats may serve as supplementary resources promoting bee populations and hence their pollination service to wild plants and crops (Kremen et al., 2007; Lander, Bebber, & Choy, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the degradation of the environment in early restoration areas may limit the availability of pollinators (Kremen et al 2007). In this sense, plants that reproduce through selfing have the advantage of reproductive assurance (Pannell & Barrett 1998;Moeller & Geber 2005;Santos et al 2012), but may suffer disadvantages related to high inbreeding rates (Lande & Schemske 1985;Herlihy & Eckert 2002;Maia et al 2017).…”
Section: Introductionmentioning
confidence: 99%